Pengaruh Produk, Harga, Tempat dan Promosi Pemasaran terhadap Keputusan Pembelian Batik Tegalan Mata Canting Kelurahan Bandung, Kota Tegal - Lusi Suryani; Nur Afridah; Slamet Bambang Riono (Journal of Management and Creative Business, 2024)
This research aims: 1) To determine and analyze the influence of products on purchasing decisions for Batik Tegalan Mata Canting. 2) To find out and analyze the influence of price on purchasing decisions for Batik Tegalan Mata Canting. 3) To determine and analyze the influence of location/distribution channels i on purchasing decisions for Batik Tegalan Mata Canting.. 4) To determine and analyze the influence of promotions on purchasing decisions for Batik Tegalan Mata Canting. 5) To determine and analyze the influence of product, price , promotion, location/distribution channels on purchasing decisions for Batik Tegalan Mata Canting simultaneously. The type of research used in this research is a quantitative approach, this research has a population of 800 by taking a sample of 90 respondents. Based on the analysis and discussion, a conclusion can be drawn where H1: Products have a positive and significant effect on purchasing decisions, in Batik Tegalan Mata Canting, Bandung District, Tegal City. with a t-count value of 4.695 > t-table 1.662 and a sig value. 0.000 < 0.05. H2: Price has a positive and significant effect on purchasing decisions, in Batik Tegalan Mata Canting, Bandung District, Tegal City. with a t-count value of 2.349 > t-table 1.662 and a sig value. 0.028 < 0.05. H3: Place/Location has a negative and insignificant effect on purchasing decisions in Batik Tegalan Mata Canting, Bandung District, Tegal City. with a t-count value of 0.046 < t-table 1.662 and a sig. 0.064 > 0.05. H4: Promotion has a positive and significant effect on purchasing decisions, in Batik Tegalan Mata Canting, Bandung District, Tegal City. with a t-count value of 2.513 > t-table 1.662 and a sig value. 0.014 < 0.05. and H5: Product, Price, Place/Location, and Promotion simultaneously have a positive and significant effect on Purchasing Decisions in Batik Tegalan Mata Canting, Bandung District, Tegal City with F-count > F-table (24,466 > 2,706) and sig. 0.000 < 0.05.